Implementasi Kurikulum Merdeka Belajar Pendekatan Deplearning - Hartadi Hartadi; Taufiqurrohman Taufiqurrohman (TSAQOFAH, 2026)
Although the Merdeka Belajar Curriculum has been directed toward promoting independence, meaningful engagement, and contextual learning experiences, its implementation still requires a learning approach that can strengthen conceptual understanding, critical thinking, collaboration, creativity, and the application of knowledge in authentic contexts. This study aims to analyze the implementation of the Merdeka Belajar Curriculum through a deep learning approach, identify supporting and inhibiting factors, and examine its implications for improving learning quality. This study used a qualitative approach with a case study design. Data were collected through classroom observations, semi-structured interviews with the principal, teachers, and students, as well as documentation analysis of teaching modules, learning activities, and assessment instruments. The data were analyzed through data reduction, data display, and conclusion drawing using an interactive analysis model. The results showed that the deep learning approach supported the implementation of the Merdeka Belajar Curriculum through student-centered learning, inquiry-based activities, collaborative problem solving, differentiated learning, and authentic assessment. Teachers play an important role in designing learning experiences that connect academic material with real-life situations and students’ needs. The main challenges in implementing this approach include differences in teachers’ pedagogical competence, limited learning resources, limited time, and uneven student readiness. The conclusion of this study affirms that the deep learning approach strengthens the orientation of the Merdeka Belajar Curriculum toward holistic student development, particularly in cognitive, social, emotional, and character dimensions. The implications of this study include the importance of continuous teacher professional development, institutional support, the provision of adaptive learning resources, and an evaluation system capable of measuring higher-order thinking skills and meaningful learning outcomes.